Recent advances in immune checkpoint inhibitors for non-small lung cancer treatment - Altaf, Reem; Jadoon, Sarmad Sheraz; Muhammad, Syed Aun; Ilyas, Umair; Duan, Yongtao (Frontiers in Oncology, 2022)
Lung cancer is one of the deadliest types of cancer responsible for thousands of cancer-related deaths. Its treatment has remained a challenge for researchers, but an increase in the knowledge of molecular pathways and biology of lung cancer has dramatically changed its management in recent decades. Immunotherapies and immunomodulation of lung cancer have previously failed for a long time but thanks to continuous research work and enthusiasm, now this field is emerging as a novel effective therapy. Now, it is hope with potential benefits and promising results in the treatment of lung cancer. This review article focuses on immune checkpoints inhibitors; CTLA-4 inhibitors (ipilimumab and Tremelimumab) and PDL-1 inhibitors (durvalumab, atezolizumab) that can be blocked to treat lung carcinoma. It is also focused on critically analyzing different studies and clinical trials to determine the potential benefits, risks, and adverse events associated with immunotherapeutic treatment.